Effect of Some Plant Extracts on Isolated Bacteria from Eyelids of Natural Eye liner Users and Eye Cosmetics Users - Hero Farhad Salah Akrayi (Journal of Applied Pharmaceutical Science)
This study includes isolation of bacteria from eyelids of ten females use eye cosmetic (A) and ten from those use natural eyeliner (B) in addition to those do not use any things (C: male (3) and female (7)) by swab taken from students of college of Education/ Scientific Dept.-Biology Dept. The bacteria identified depending on cultural, morphological and some biochemical properties and according to their identity they included (S. aurus and S. epidermidis where the percentage of each of them was 40%, 40% and 20% for group A, B and C respectively and S. capitis was 30%, 10% and 60% for group A, B and C), while the Gram negative isolates represented with E. coli where the percentage was 70% and 30% for group A and B. Antibacterial activity of nine aqueous plant extracts was tested against twenty selected isolates.. All isolates did not show any susceptibility against extract of ginger and less susceptibility against nutmeg and senna. While all isolates showed moderate sensitivity against the extract of coriander. The antibacterial activity of each of fennel, cubeb and turmeric had a strong effect against the isolates, while black tea and black dry lime extracts showed more strongly effect against growth of isolates. The results showed that E. coli isolates were more resistance against the most extracts and in different concentrations comparing with other isolates.
Keywords: Eyelid, Bacteria, Antibacterial, Plant extracts, Natural eyeliner, Cosmetic.